Co-encapsulation of Nigella sativa oil and plasmid DNA for enhanced gene therapy of Alzheimer’s disease - Doolaanea, Abd Almonem; Mansor, Nur 'Izzati; Mohd Nor, Nurul Hafizah; Mohamed, Farahidah (TAYLOR & FRANCIS LTD, 2016)
Alzheimer disease involves genetic and non-genetic factors and hence it is rational to be treated with genetic and non-genetic therapeutic agents. Nigella sativa has multiple therapeutic properties including neuroregeneration. Nigella sativa oil (NSO) was encapsulated in PLGA nanoparticles and pDNA was loaded either by adsorption on chitosan-modified particles or encapsulation within PLGA nanoparticles. The particle size and zeta potential of NSO-pDNA-chitosan-PLGA nanoparticles were highly dependent on the medium and exhibited high burst release. Meanwhile, NSO-pDNA-PLGA nanoparticles were more consistent with lower burst release. The fabricated nanoparticles revealed the expected outcomes of both pDNA and NSO. The pDNA transfected N2a cell while the encapsulated NSO promoted neurite outgrowth that is crucial for neuroregeneration. Results from this study suggest that NSO could be added to the gene delivery carrier to enhance treatment benefits for Alzheimer disease.